High-strength nylon composite material and preparation method thereof
Through multi-stage interface engineering and reasonable assembly and distribution ratio, a high-strength nylon composite material was developed, which solved the problem of insufficient strength of traditional nylon materials, achieved strength improvement and toughness maintenance, and was suitable for high-demand engineering applications.
Patent Information
- Application Number
- CN202510196145.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional nylon materials have limitations in strength and are difficult to meet the high-strength needs in fields such as aerospace and high-end machinery. At the same time, the existing methods to improve the strength of nylon materials often lead to other performance degradation, and the preparation process is complex and costly.
Through multi-stage interface engineering and reasonable composition and distribution ratio, a high-strength nylon composite material was developed, including nylon, modified graphene oxide, modified glass fiber, toughening agent, lubricant and antioxidant, and granulated by twin-screw extruder, achieving strength enhancement and toughness retention.
It realizes the toughness of nylon composite materials while increasing strength, and provides a high-performance composite material with balanced comprehensive performance and high reliability, suitable for high-demand engineering applications.
Smart Images

Figure BDA0005281552830000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a high-strength nylon composite material and a preparation method thereof. Background Art
[0002] As an important engineering plastic, nylon (polyamide) is widely used in the fields of automobiles, electronic appliances, machinery manufacturing, aerospace, etc. due to its excellent mechanical properties, wear resistance, chemical corrosion resistance and processing convenience. For example, in automotive parts, nylon is used to manufacture engine peripheral parts, interior parts and transmission parts; in the field of electronic appliances, nylon is often used to make housings, connectors, etc.
[0003] However, as various industries continue to increase their requirements for material performance, traditional nylon materials have gradually exposed some limitations in terms of strength. In some application scenarios that require extremely high material strength, such as structural parts in the aerospace field and key transmission parts of high-end machinery, the strength of ordinary nylon materials is difficult to meet actual needs, which limits the further application and development of nylon materials in these fields.
[0004] In addition, existing methods for improving the strength of nylon materials have many shortcomings. Although some methods can improve the strength to a certain extent, they often lead to a decrease in other properties of the material, such as toughness and processing performance. In addition, the preparation process is complicated and costly, which is not conducive to large-scale industrial production.
[0005] Therefore, developing a high-strength nylon composite material and a preparation method thereof to meet the needs of various industries for high-strength, high-performance nylon materials and overcome the defects of the existing technology has important practical significance and broad market prospects. Summary of the invention
[0006] Based on the problems existing in the background technology, the present invention provides a high-strength nylon composite material and a preparation method thereof. Through multi-level interface engineering and reasonable component ratio, the high strength is improved while maintaining the excellent toughness of the nylon composite material, thereby providing a high-performance composite material solution with balanced comprehensive performance and high reliability for engineering applications.
[0007] The present invention is implemented by the following technical solutions:
[0008] A high-strength nylon composite material comprises the following raw materials by weight: 40-65 parts of nylon, 1-5 parts of modified graphene oxide, 5-15 parts of modified glass fiber, 1-5 parts of toughening agent, 0.1-1 parts of lubricant and 0.1-1 parts of antioxidant.
[0009] Furthermore, the nylon is at least one of nylon 6 or nylon 66.
[0010] Furthermore, the preparation method of the modified graphene oxide specifically comprises the following steps:
[0011] S11. adding graphene oxide to N,N-dimethylformamide and dispersing by ultrasonication to obtain a graphene oxide dispersion;
[0012] S12. dissolving 4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride in N,N-dimethylamide to obtain a 4,4'-diaminobiphenyl solution and a 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution;
[0013] S13. placing graphene oxide in a reactor, adding 4,4'-diaminobiphenyl solution under nitrogen protection, stirring evenly, adding 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution dropwise under ice bath conditions, heating to room temperature, stirring to react for 1-2h, and continuing to heat to 65°C, reacting for 4-5h to obtain a reaction solution;
[0014] Wherein, step S13 comprises:
[0015] Step S131: After loading the graphene oxide suspension in the reactor, the initial temperature distribution of the reaction system is monitored in real time by a multi-point temperature sensor integrated on the inner wall of the reactor;
[0016] Step S132: when injecting the 4,4'-diaminobiphenyl solution into the reactor, start the PID feedback control system, dynamically adjust the flow rate of the cooling medium circulation pump according to the preset ice bath temperature setting value, so that the temperature of the reaction system is stabilized in the range of 0-5°C;
[0017] Step S133: under ice bath conditions, adding 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution dropwise at a flow rate of 0.5-2 mL / min by a precision peristaltic pump, while maintaining a stirring speed of 800-1200 rpm by a magnetic stirrer;
[0018] Step S134: When the infrared spectrum sensor detects that the intensity of the characteristic peak of the anhydride reaches a preset threshold, the temperature gradient control module is triggered to raise the temperature of the system to 25°C at a rate of 1°C / min, and the heat exchange power of the jacket heat exchanger is adjusted by the PID controller;
[0019] Step S135: When the temperature rises to 65° C., the stirring rate and the heating power are dynamically adjusted according to the pH value and ion concentration data fed back in real time by the electrochemical sensor, so that the conductivity of the reaction solution is maintained in the optimized range of 50-200 μS / cm;
[0020] Step S136: When the near infrared spectrometer detects that the intensity of the characteristic absorption peak of the imine bond reaches the target value, and the temperature sensor shows that the system temperature fluctuation is less than ±0.5°C for 30 minutes, the reaction is determined to be complete and the heating is terminated;
[0021] In step S131, the initial temperature distribution of the reaction system is monitored in real time by a multi-point temperature sensor integrated on the inner wall of the reactor, including:
[0022] A first temperature data set is collected in real time at different spatial positions in the reaction system by using a plurality of temperature sensors; the first temperature data set is used to generate an initial temperature distribution map;
[0023] Extract temperature characteristic parameters according to the initial temperature distribution map, including the temperature mean, standard deviation and temperature gradient extreme value of each area; divide the interior of the reactor into a high temperature compensation area, a low temperature compensation area and a steady-state maintenance area based on the difference between the temperature mean and the preset standard temperature range;
[0024] Determine whether the temperature standard deviation of the high / low temperature compensation area exceeds the first set threshold, and whether the temperature gradient extreme value exceeds the second set threshold; if exceeded, mark the corresponding area as an abnormal temperature field area and assign an adjustment priority;
[0025] The dynamic compensation strategy is started according to the adjustment priority. If the priority of the high temperature compensation zone is higher than that of the low temperature compensation zone, the circulating cooling unit of the reactor is activated, and the flow rate of the cooling medium is adjusted based on the direction of the extreme value of the temperature gradient; if the priority of the low temperature compensation zone is higher, the heating module and the stirring device are coordinated to adjust the heating power and stirring rate according to the ratio of the temperature difference between the zones;
[0026] Acquire the compensated second temperature data set in real time, and reconstruct the updated temperature distribution map until the temperature standard deviation of all regions is lower than the first set threshold and the temperature gradient extreme value drops to within the second set threshold, and it is determined that the initial temperature uniformity condition is met;
[0027] The step S135 of dynamically adjusting the stirring rate and the heating power includes:
[0028] A three-dimensional response surface model of pH-temperature-conductivity was established. When the pH value was detected to be outside the range of 6.5-7.5:
[0029] If pH < 6.5, increase the stirring rate by 5% for every 0.1 pH unit decrease and reduce the heating power by 2%;
[0030] If pH>7.5, the stirring rate is reduced by 3% for every 0.1 pH unit increase, and the heating power is increased by 1.5%; S14. The reaction solution is cooled to room temperature, then poured into deionized water for precipitation, filtered, washed, and dried to obtain modified graphene oxide.
[0031] Furthermore, in the preparation process, the molar ratio of 4,4'-diaminobiphenyl to 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride is 1:1; and the amount of graphene oxide used is 10-40% by weight of the total amount of 4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride used.
[0032] Furthermore, the preparation method of the modified glass fiber is specifically as follows:
[0033] S21. The glass fiber was immersed in a 5% sodium hydroxide solution for 2-3h and dried to obtain a pretreated glass fiber;
[0034] S22. The pretreated glass fiber is transferred to a zinc acetate solution and subjected to a hydrothermal reaction for 4-5 hours to obtain a pre-modified glass fiber;
[0035] S23. dopamine was added to a pH 8.5 Tris buffer to obtain a dopamine solution; maleic anhydride was dissolved in dimethyl sulfoxide to obtain a maleic anhydride solution; the maleic anhydride solution was added to the dopamine solution, stirred and mixed under nitrogen protection, and then dimethyldiallylammonium chloride and ammonium persulfate were added to obtain a modified solution;
[0036] S24. Soak the pre-modified glass fiber in the modifying liquid, heat and stir, and then wash and dry to obtain the modified glass fiber.
[0037] Furthermore, in step S22, the concentration of zinc acetate is 0.1 M, and the reaction temperature is 65-75°C.
[0038] Furthermore, in step S23, the dopamine concentration is 1.5-2 mol / L; the maleic anhydride concentration is 1-1.5 mol / L; the molar ratio of dopamine, maleic anhydride and dimethyldiallyl ammonium chloride is 1:(1-1.5):(0.5-1.5); and the amount of ammonium persulfate used is 3-8% by weight of the total amount of dopamine and dimethyldiallyl ammonium chloride used.
[0039] Furthermore, in step S24, the heating temperature is 40-60° C., and the stirring time is 10-30 min.
[0040] Further, it is characterized in that the toughening agent is at least one of polyoctene-maleic anhydride graft, ethylene-ethyl acrylate copolymer and ethylene-methyl acrylate copolymer grafted glycidyl acrylate copolymer;
[0041] The lubricant is at least one of ethylene bis stearamide, silicone powder, and pentaerythritol stearate;
[0042] The antioxidant is at least one of hindered phenols or phosphorus-containing antioxidants.
[0043] The present invention also discloses a method for preparing the high-strength nylon composite material, comprising the following steps:
[0044] S1. preparing modified graphene oxide;
[0045] S2. Preparation of modified glass fiber;
[0046] S3. Put nylon, modified graphene oxide, modified glass fiber, toughening agent, lubricant and antioxidant into a mixer and mix them evenly. Then add the mixture into the feeding port of a twin-screw extruder. The six-section temperatures in the twin-screw extruder are 210°C, 220°C, 230°C, 230°C, 220°C and 210°C. After extrusion and granulation, a high-strength nylon composite material is obtained.
[0047] Among them, the S3 step includes:
[0048] S31: inputting nylon, modified graphene oxide, modified glass fiber, toughening agent, lubricant and antioxidant into a mixing device according to a preset ratio for dry mixing to obtain a uniform mixture;
[0049] S32: adding the mixed material from the feeding port of the twin-screw extruder, and performing gradient heating through six independent temperature control sections, wherein the first to sixth temperature control sections are set to 210° C., 220° C., 230° C., 230° C., 220° C., and 210° C., respectively; each temperature control section is equipped with an independent thermocouple and PID control system to collect the actual temperature value in real time and perform closed-loop feedback adjustment with the set value;
[0050] S33: a melt pressure sensor is arranged at the outlet of the feed port to monitor the melt pressure value during the extrusion process in real time; when it is detected that the pressure value exceeds the preset safety range, a pressure abnormality signal is triggered and a linkage control strategy is executed;
[0051] S4. When the melt pressure value returns to the safe range and lasts for more than the set time, restart the feeding and restore the original speed of the main drive motor to complete the granulation process.
[0052] The linkage control strategy in step S33 includes:
[0053] Match the corresponding alarm level according to the type of abnormal pressure signal, where a level 1 alarm is triggered when the pressure value exceeds the upper threshold, and a level 2 alarm is triggered when the pressure value is lower than the lower threshold;
[0054] In the first-level alarm state, the main drive motor of the twin-screw extruder is controlled to reduce the speed to the preset safety speed, and the mixing device is stopped from feeding the material to the feeding port;
[0055] In the secondary alarm state, the current speed of the main drive motor is maintained, and the auxiliary heating device in the die area is started to improve the melt fluidity;
[0056] The method for determining the preset safety range in step S33 includes:
[0057] According to the content percentage X of modified graphene oxide in the mixture and the aspect ratio Y of the modified glass fiber, a pressure threshold calculation model is established:
[0058] P max =8.5X+0.3Y+12.5
[0059] P min =6.2X+0.15Y+8.7
[0060] The value range of X is 3%-8%, and the value range of Y is 20-50;
[0061] When the real-time pressure value P real >P max It is judged as a first-level alarm when P real <P min It is judged as a level 2 alarm.
[0062] In step (3), the dopamine concentration is 1.5-2 mol / L; the maleic anhydride concentration is 1-1.5 mol / L; the molar ratio of dopamine, maleic anhydride and dimethyldiallyl ammonium chloride is 1:(1-1.5):(0.5-1.5); and the amount of ammonium persulfate used is 3-8% by weight of the total amount of dopamine and dimethyldiallyl ammonium chloride used.
[0063] The stirring time in step (3) is 12-24 hours; the heating temperature in step (4) is 40-60° C. and the stirring time is 10-30 minutes.
[0064] Beneficial effects of the present invention:
[0065] Modified graphene oxide in this application has higher specific strength and modulus, and its ultra-thin layered structure can build a continuous reinforcement network on a microscopic scale; after chemical modification, the graphene oxide surface obtains rich functional groups, which can form a good interface interaction with the nylon matrix and realize efficient transmission of stress. Glass fiber has higher rigidity and heat resistance, and its size is at the micron level, and a skeleton structure can be built macroscopically. After surface modification, the surface activity of glass fiber is improved, and a firm bonding layer is formed between the nylon matrix, further enhancing the mechanical strength of the overall structure of nylon composite materials. Modified graphene oxide mainly plays a bridging and stress dispersion role on a microscopic scale, and modified glass fiber provides a macroscopic support skeleton; the two together construct a multi-scale, continuous reinforcement network, so that the composite material can evenly disperse stress when subjected to force, which not only significantly improves tensile and bending strength, but also avoids reducing toughness due to local stress concentration. DETAILED DESCRIPTION
[0066] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.
[0067] In the examples and comparative examples of the present application, the nylon used is nylon 6, the toughening agent is polyoctene-maleic anhydride graft, the lubricant is ethylene bisstearamide, and the antioxidant is antioxidant 1010.
[0068] Example 1
[0069] A method for preparing a high-strength nylon composite material comprises the following steps:
[0070] S1. Preparation of modified graphene oxide:
[0071] S11. adding graphene oxide to N,N-dimethylformamide and dispersing by ultrasonication to obtain a graphene oxide dispersion;
[0072] S12. dissolving 4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride in N,N-dimethylamide to obtain a 4,4'-diaminobiphenyl solution and a 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution;
[0073] S13. placing graphene oxide in a reactor, adding 4,4'-diaminobiphenyl solution under nitrogen protection, stirring evenly, adding 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution dropwise under ice bath conditions, heating to room temperature, stirring to react for 1-2h, and continuing to heat to 65°C, reacting for 4-5h to obtain a reaction solution;
[0074] S14. The reaction solution is cooled to room temperature, then poured into deionized water for precipitation, filtered, washed, and dried to obtain modified graphene oxide.
[0075] During the preparation process, the molar ratio of 4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride is 1:1; the amount of graphene oxide used is 20% of the total weight of 4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride.
[0076] S2. Preparation of modified glass fiber:
[0077] S21. The glass fiber was immersed in a 5% sodium hydroxide solution for 2-3h and dried to obtain a pretreated glass fiber;
[0078] S22. The pretreated glass fiber was transferred to a 0.1 M zinc acetate solution and subjected to a hydrothermal reaction at 70° C. for 4 h to obtain a pre-modified glass fiber;
[0079] S23. Add dopamine to pH 8.5 Tris buffer to obtain a dopamine solution with a concentration of 2 mol / L; dissolve maleic anhydride in dimethyl sulfoxide to obtain a maleic anhydride solution with a concentration of 1.5 mol / L; add the maleic anhydride solution to the dopamine solution, stir and mix evenly under nitrogen protection, then add dimethyldiallylammonium chloride and ammonium persulfate, and continue stirring for 16 hours to obtain a modified solution; wherein the molar ratio of dopamine, maleic anhydride and dimethyldiallylammonium chloride is 1:1.2:1; the amount of ammonium persulfate used is 5% by weight of the total amount of dopamine and dimethyldiallylammonium chloride used.
[0080] S24. Soak the pre-modified glass fiber in the modifying liquid, heat to 50°C and stir for 20 minutes. After completion, wash and dry to obtain the modified glass fiber.
[0081] S3. By weight, 60 parts of nylon, 3 parts of modified graphene oxide, 10 parts of modified glass fiber, 2 parts of toughening agent, 0.5 part of lubricant and 0.5 part of antioxidant are put into a mixer and mixed evenly. Then the mixture is added from the feeding port of a twin-screw extruder. The six-section temperatures in the twin-screw extruder are 210°C, 220°C, 230°C, 230°C, 220°C and 210°C. After extrusion and granulation, a high-strength nylon composite material is obtained.
[0082] Example 2
[0083] A method for preparing a high-strength nylon composite material comprises the following steps:
[0084] S1. Preparation of modified graphene oxide: same as in Example 1;
[0085] S2. Preparation of modified glass fiber: Same as in Example 1;
[0086] S3. By weight, 60 parts of nylon, 5 parts of modified graphene oxide, 10 parts of modified glass fiber, 2 parts of toughening agent, 0.5 part of lubricant and 0.5 part of antioxidant are put into a mixer and mixed evenly. Then the mixture is added from the feeding port of a twin-screw extruder. The six-section temperatures in the twin-screw extruder are 210°C, 220°C, 230°C, 230°C, 220°C and 210°C. After extrusion and granulation, a high-strength nylon composite material is obtained.
[0087] Example 3
[0088] A method for preparing a high-strength nylon composite material comprises the following steps:
[0089] S1. Preparation of modified graphene oxide: same as in Example 1;
[0090] S2. Preparation of modified glass fiber: Same as in Example 1;
[0091] S3. By weight, 60 parts of nylon, 3 parts of modified graphene oxide, 15 parts of modified glass fiber, 2 parts of toughening agent, 0.5 part of lubricant and 0.5 part of antioxidant are put into a mixer and mixed evenly. Then the mixture is added from the feeding port of a twin-screw extruder. The six-section temperatures in the twin-screw extruder are 210°C, 220°C, 230°C, 230°C, 220°C and 210°C. After extrusion and granulation, a high-strength nylon composite material is obtained.
[0092] Example 4
[0093] Step S13 includes:
[0094] Step S131: After loading the graphene oxide suspension in the reactor, the initial temperature distribution of the reaction system is monitored in real time by a multi-point temperature sensor integrated on the inner wall of the reactor;
[0095] Step S132: when injecting the 4,4'-diaminobiphenyl solution into the reactor, start the PID feedback control system, dynamically adjust the flow rate of the cooling medium circulation pump according to the preset ice bath temperature setting value, so that the temperature of the reaction system is stabilized in the range of 0-5°C;
[0096] Step S133: under ice bath conditions, adding 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution dropwise at a flow rate of 0.5-2 mL / min by a precision peristaltic pump, while maintaining a stirring speed of 800-1200 rpm by a magnetic stirrer;
[0097] Step S134: When the infrared spectrum sensor detects that the intensity of the characteristic peak of the anhydride reaches a preset threshold, the temperature gradient control module is triggered to raise the temperature of the system to 25°C at a rate of 1°C / min, and the heat exchange power of the jacket heat exchanger is adjusted by the PID controller;
[0098] Step S135: When the temperature rises to 65° C., the stirring rate and the heating power are dynamically adjusted according to the pH value and ion concentration data fed back in real time by the electrochemical sensor, so that the conductivity of the reaction solution is maintained in the optimized range of 50-200 μS / cm;
[0099] Step S136: When the near infrared spectrometer detects that the intensity of the characteristic absorption peak of the imine bond reaches the target value, and the temperature sensor shows that the system temperature fluctuation is less than ±0.5°C for 30 minutes, the reaction is determined to be complete and the heating is terminated;
[0100] In step S131, the initial temperature distribution of the reaction system is monitored in real time by a multi-point temperature sensor integrated on the inner wall of the reactor, including:
[0101] A first temperature data set is collected in real time at different spatial positions in the reaction system by using a plurality of temperature sensors; the first temperature data set is used to generate an initial temperature distribution map;
[0102] Extract temperature characteristic parameters according to the initial temperature distribution map, including the temperature mean, standard deviation and temperature gradient extreme value of each area; divide the interior of the reactor into a high temperature compensation area, a low temperature compensation area and a steady-state maintenance area based on the difference between the temperature mean and the preset standard temperature range;
[0103] Determine whether the temperature standard deviation of the high / low temperature compensation area exceeds the first set threshold, and whether the temperature gradient extreme value exceeds the second set threshold; if exceeded, mark the corresponding area as an abnormal temperature field area and assign an adjustment priority;
[0104] The dynamic compensation strategy is started according to the adjustment priority. If the priority of the high temperature compensation zone is higher than that of the low temperature compensation zone, the circulating cooling unit of the reactor is activated, and the flow rate of the cooling medium is adjusted based on the direction of the extreme value of the temperature gradient; if the priority of the low temperature compensation zone is higher, the heating module and the stirring device are coordinated to adjust the heating power and stirring rate according to the ratio of the temperature difference between the zones;
[0105] Acquire the compensated second temperature data set in real time, and reconstruct the updated temperature distribution map until the temperature standard deviation of all regions is lower than the first set threshold and the temperature gradient extreme value drops to within the second set threshold, and it is determined that the initial temperature uniformity condition is met;
[0106] The step S135 of dynamically adjusting the stirring rate and the heating power includes:
[0107] A three-dimensional response surface model of pH-temperature-conductivity was established. When the pH value was detected to be outside the range of 6.5-7.5:
[0108] If pH < 6.5, increase the stirring rate by 5% for every 0.1 pH unit decrease and reduce the heating power by 2%;
[0109] If pH>7.5, reduce stirring rate by 3% for every 0.1 pH unit increase and increase heating power by 1.5%.
[0110] The principle and beneficial effects of the above scheme are as follows: graphene oxide powder is dispersed in an appropriate amount of solvent, ultrasonically treated to ensure uniform dispersion, and then the suspension is loaded into the reactor; graphene oxide has excellent dispersibility and adjustable surface properties, so it needs to be dispersed in the solution to increase its surface area and improve the efficiency of subsequent reactions. After loading, the temperature distribution of the system is monitored by the temperature sensor on the inner wall of the reactor to ensure that the temperature control of the subsequent reaction is accurate. A 4,4'-diaminobiphenyl solution of a predetermined concentration is injected into the reactor. During this process, the PID feedback control system is started, and the flow rate of the cooling medium circulation pump is dynamically adjusted according to the temperature value set by the ice bath in the reactor to ensure that the temperature of the reaction system remains in the range of 0-5°C; the 4,4'-diaminobiphenyl solution needs to react in a low temperature environment to avoid excessive reaction rate and the occurrence of side reactions. The cooling medium flow rate is controlled by the PID feedback system, which can accurately control the reaction temperature and provide stable conditions for subsequent reactions. Use a precision peristaltic pump to drop 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution into the reaction system at a flow rate of 0.5-2mL / min. At the same time, stir the reaction system to 800-1200rpm by a magnetic stirrer to ensure uniform mixing of the reactants. The dropwise addition process controls the reaction rate, helps to maintain the balance between temperature and reactant concentration, and avoids the formation of by-products due to too fast reaction. Stirring can promote full contact between reactants and improve reaction efficiency. When the infrared spectrum sensor detects that the characteristic peak intensity of the anhydride reaches the preset threshold, the temperature gradient control module is triggered to raise the system temperature to 25°C at a rate of 1°C / min, and the heat exchange power of the jacket heat exchanger is adjusted by the PID controller to ensure the stability of the temperature rise. When the characteristic peak of the anhydride appears, it indicates that the reaction has reached a certain stage. At this time, it is necessary to gradually increase the temperature to promote the reaction. Slow heating helps control the reaction rate and prevent unnecessary side reactions caused by overheating. When the temperature rises to 65°C, the stirring rate and heating power are dynamically adjusted according to the real-time data provided by the electrochemical sensor, such as pH value and ion concentration. By monitoring the conductivity, the reaction system is kept within the conductivity range of 50-200μS / cm to ensure the optimal efficiency of the reaction. The pH value and conductivity of the reaction solution directly affect the reaction process and the quality of the product. According to the real-time monitoring data, by adjusting the stirring rate and heating power, the reaction environment can be effectively controlled to maintain the optimal reaction conditions. When the near-infrared spectrometer detects that the intensity of the characteristic absorption peak of the imine bond reaches the target value, and the temperature sensor shows that the fluctuation of the system temperature is less than ±0.5°C and lasts for 30 minutes, the reaction is considered to be completed, and the heating is stopped and the reaction is terminated. By monitoring the intensity of the characteristic absorption peak of the imine bond, it is possible to accurately judge whether the reaction is completed. A temperature fluctuation of less than ±0.5°C indicates that the reaction system has stabilized, ensuring that the reaction is completely completed and the product quality is stable.During the entire reaction process, attention is paid to the fine adjustment of temperature control, stirring and reactant drop rate in order to ensure the stability of reaction conditions, maximize product formation and avoid side reactions. Dynamic adjustment of key factors such as conductivity, pH value, temperature and flow rate of the reaction solution helps to optimize the reaction path and ensure the performance and quality of the final product.
[0111] Example 5
[0112] Among them, the S3 step includes:
[0113] S31: inputting nylon, modified graphene oxide, modified glass fiber, toughening agent, lubricant and antioxidant into a mixing device according to a preset ratio for dry mixing to obtain a uniform mixture;
[0114] S32: adding the mixed material from the feeding port of the twin-screw extruder, and performing gradient heating through six independent temperature control sections, wherein the first to sixth temperature control sections are set to 210° C., 220° C., 230° C., 230° C., 220° C., and 210° C., respectively; each temperature control section is equipped with an independent thermocouple and PID control system to collect the actual temperature value in real time and perform closed-loop feedback adjustment with the set value;
[0115] S33: a melt pressure sensor is arranged at the outlet of the feed port to monitor the melt pressure value during the extrusion process in real time; when it is detected that the pressure value exceeds the preset safety range, a pressure abnormality signal is triggered and a linkage control strategy is executed;
[0116] S4. When the melt pressure value returns to the safe range and lasts for more than the set time, restart the feeding and restore the original speed of the main drive motor to complete the granulation process.
[0117] The linkage control strategy in step S33 includes:
[0118] Match the corresponding alarm level according to the type of abnormal pressure signal, where a level 1 alarm is triggered when the pressure value exceeds the upper threshold, and a level 2 alarm is triggered when the pressure value is lower than the lower threshold;
[0119] In the first-level alarm state, the main drive motor of the twin-screw extruder is controlled to reduce the speed to the preset safety speed, and the mixing device is stopped from feeding the material to the feeding port;
[0120] In the secondary alarm state, the current speed of the main drive motor is maintained, and the auxiliary heating device in the die area is started to improve the melt fluidity;
[0121] The method for determining the preset safety range in step S33 includes:
[0122] According to the content percentage X of modified graphene oxide in the mixture and the aspect ratio Y of the modified glass fiber, a pressure threshold calculation model is established:
[0123] P max =8.5X+0.3Y+12.5
[0124] P min =6.2X+0.15Y+8.7
[0125] The value range of X is 3%-8%, and the value range of Y is 20-50;
[0126] When the real-time pressure value P real >P max It is judged as a first-level alarm when P real <P min It is judged as a level 2 alarm.
[0127] The principle and beneficial effects of the above scheme are as follows: First, nylon, modified graphene oxide, modified glass fiber, toughening agent, lubricant and antioxidant are added to the mixing device for dry mixing according to the preset ratio. The precise control of the ratio of each raw material is to ensure the consistency of material performance and the characteristics of the composite material. The purpose of dry mixing is to mix all raw materials evenly and ensure that the properties of each part of the composite material can be fully utilized. This process plays a key role in the dispersion and fluidity of the material. The mixed material after uniform dry mixing is added to the feeding port of the twin-screw extruder. The twin-screw extruder is an efficient plastic processing equipment. Its structural characteristics enable it to efficiently mix and heat the material in a short time. After entering the extruder, the mixed material is heated by six temperature control sections. The temperatures of the temperature control sections are set to 210℃, 220℃, 230℃, 230℃, 220℃, and 210℃ respectively. Such a temperature gradient helps to control the viscosity and fluidity of the melt and ensure the stability of the material during the extrusion process. Each temperature control section has an independent thermocouple and PID control system, which can collect the actual temperature value in real time and perform closed-loop feedback adjustment with the set temperature value to ensure accurate temperature control and avoid affecting the quality of the composite material due to temperature fluctuations. A melt pressure sensor is set at the outlet of the feed port to monitor the melt pressure value in real time. Pressure is an important indicator in the extrusion process. It can reflect the fluidity of the material and the problems in the extrusion process. If the pressure exceeds the preset safety range, the system will trigger a pressure abnormality signal and start the linkage control strategy. By monitoring the pressure value in real time, potential abnormal problems can be discovered in time, and control strategies can be used to avoid equipment damage or material quality problems.
[0128] Different control measures are taken according to the changes in the melt pressure value: Level 1 alarm: When the real-time pressure value exceeds the upper threshold, the level 1 alarm is triggered. At this time, the speed of the main drive motor of the twin-screw extruder is reduced to the preset safe speed, and the extrusion rate is reduced to avoid further pressure increase. At the same time, the mixing device stops feeding the feed port to prevent excessive material from entering and causing pressure to exceed the standard. Level 2 alarm: When the real-time pressure value is lower than the lower threshold, the level 2 alarm is triggered. In this state, the current speed of the main drive motor is maintained to ensure the continuity of production, and the auxiliary heating device in the die area is started to improve the fluidity of the melt and avoid the melt from being too viscous, thereby ensuring a smooth extrusion process. According to the percentage of modified graphene oxide content (X) and the aspect ratio (Y) of the modified glass fiber in the mixture, the safe pressure threshold is calculated by formula. These values are obtained through experiments or simulation models to ensure the stability of the composite material during extrusion.
[0129] P max : Upper limit of pressure, the formula is P max =8.5X+0.3Y+12.5, when the real-time pressure value exceeds this upper limit, the first level alarm is triggered. min : Pressure lower limit, formula is P min =6.2X+0.15Y+8.7. When the real-time pressure value is lower than this lower limit, the secondary alarm is triggered. These calculation formulas are based on the content of modified graphene oxide and the aspect ratio of glass fiber, which are related to the melt characteristics of the material, so the pressure threshold can be accurately set.
[0130] When the melt pressure value returns to the safe range and lasts for more than the set time, the system will restart the feeding and restore the original speed of the main drive motor to continue the process operation. This process ensures the continuity and stability of the production process, while also avoiding production interruptions or equipment damage caused by abnormal pressure. After all the above steps, the final composite material is a high-strength nylon composite material. Through the efficient heating, mixing and granulation of the twin-screw extruder, the material has excellent mechanical properties and fluidity, and is suitable for various high-demand industrial applications.
[0131] Comparative Example 1
[0132] A preparation method of a nylon composite material comprises the following steps: by weight, 60 parts of nylon, 3 parts of unmodified graphene oxide, 10 parts of unmodified glass fiber, 2 parts of a toughening agent, 0.5 parts of a lubricant and 0.5 parts of an antioxidant are put into a mixer and mixed evenly; then the mixture is added from a feeding port of a twin-screw extruder, wherein the temperatures of six sections in the twin-screw extruder are 210° C., 220° C., 230° C., 230° C., 220° C. and 210° C.; and after extrusion and granulation, a high-strength nylon composite material is obtained.
[0133] The difference between this comparative example and Example 1 is that unmodified graphene oxide and unmodified glass fiber are used.
[0134] Comparative Example 2
[0135] A preparation method of a nylon composite material comprises the following steps: by weight, 60 parts of nylon, 3 parts of unmodified graphene oxide, 10 parts of modified glass fiber, 2 parts of a toughening agent, 0.5 parts of a lubricant and 0.5 parts of an antioxidant are put into a mixer and mixed evenly; then the mixture is added from a feeding port of a twin-screw extruder; the temperatures of six sections in the twin-screw extruder are 210° C., 220° C., 230° C., 230° C., 220° C. and 210° C.; and after extrusion and granulation, a high-strength nylon composite material is obtained.
[0136] The difference between this comparative example and Example 1 is that unmodified graphene oxide is used.
[0137] Comparative Example 3
[0138] A preparation method of a nylon composite material comprises the following steps: by weight, 60 parts of nylon, 3 parts of modified graphene oxide, 10 parts of unmodified glass fiber, 2 parts of a toughening agent, 0.5 parts of a lubricant and 0.5 parts of an antioxidant are put into a mixer and mixed evenly; then the mixture is added from a feeding port of a twin-screw extruder; the temperatures of six sections in the twin-screw extruder are 210° C., 220° C., 230° C., 230° C., 220° C. and 210° C.; and after extrusion and granulation, a high-strength nylon composite material is obtained.
[0139] The difference between this comparative example and Example 1 is that unmodified glass fiber is used.
[0140] Comparative Example 4
[0141] A preparation method of a nylon composite material comprises the following steps: by weight, 60 parts of nylon, 13 parts of modified graphene oxide, 2 parts of a toughening agent, 0.5 parts of a lubricant and 0.5 parts of an antioxidant are put into a mixer and mixed evenly; then the mixture is added from a feeding port of a twin-screw extruder; the temperatures of six sections in the twin-screw extruder are 210° C., 220° C., 230° C., 230° C., 220° C. and 210° C.; and after extrusion and granulation, a high-strength nylon composite material is obtained.
[0142] The difference between this comparative example and Example 1 is that, based on the original formula of Example 1, all that is added is modified graphene oxide, and no modified glass fiber is added.
[0143] Comparative Example 5
[0144] A preparation method of a nylon composite material comprises the following steps: by weight, 60 parts of nylon, 13 parts of modified glass fiber, 2 parts of a toughening agent, 0.5 parts of a lubricant and 0.5 parts of an antioxidant are put into a mixer and mixed evenly; then the mixture is added from a feeding port of a twin-screw extruder; the temperatures of six sections in the twin-screw extruder are 210° C., 220° C., 230° C., 230° C., 220° C. and 210° C.; and after extrusion and granulation, a high-strength nylon composite material is obtained.
[0145] The difference between this comparative example and Example 1 is that all modified glass fibers are added on the basis of the original formula of Example 1, and no modified graphene oxide is added.
[0146] Test example
[0147] The nylon composite materials prepared in Examples 1-3 and Comparative Examples 1-5 were sampled and injection molded into standard specimens, and their tensile strength (ASTM D638), elongation at break (ASTM D638), flexural strength (ASTM D790), flexural modulus (ASTM D790), and notched impact strength (ASTM D256) were tested. The test results are shown in Table 1.
[0148] Table 1
[0149]
[0150] It can be seen from the data in Table 1 that the nylon composite materials prepared in Examples 1-3 of the present invention improve strength while maintaining relatively excellent toughness. In Example 2 and Example 3, the amount of modified graphene oxide and modified oxidized glass fiber was appropriately increased, and it was found that the strength of the composite nylon material was improved to a certain extent, but the corresponding elongation at break and notched impact strength were slightly reduced. In Comparative Example 1, unmodified filler was used, the interface bonding of the unmodified filler was poor, the filler agglomeration reduced the reinforcement effect, the stress transfer efficiency was low, and the overall strength performance was greatly reduced; the elongation at break caused interface slip due to the difference in interface bonding, and the debonding of the filler-matrix interface provided additional deformation, and the deformation could be fully developed, resulting in an increase in elongation at break; the reason for the reduction in notched impact strength is that the interface slip mechanism cannot be fully utilized in dynamic testing, the high filling amount reduces the energy absorption capacity of the material, and the increased number of interfaces is more likely to become the starting point of cracks. In Comparative Examples 2 and 3, only one filler was modified, and it can be clearly seen that the strength of the nylon material has increased. In Comparative Example 4, only modified graphene oxide is used, which lacks the orientation effect of fiber reinforcement. The modified graphene oxide improves the strength but has limited reinforcement. The high content of modified graphene oxide leads to too many interfaces, and the toughness retention is not as good as in the embodiment. In Comparative Example 5, only modified glass fiber is used. The nylon composite material is slightly better than in the embodiment in terms of strength improvement, but is obviously not as good as in the embodiment in terms of toughness retention. The modified glass fiber provides rigidity contribution, lacks the toughening effect of micron filler, greatly reduces deformation capacity, and reduces elongation at break; during the notched impact strength test, the stress is concentrated at the end of the glass fiber, and the toughness is also significantly reduced.
[0151] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high-strength nylon composite material, characterized in that: The raw materials include the following components by weight: 40-65 parts of nylon, 1-5 parts of modified graphene oxide, 5-15 parts of modified glass fiber, 1-5 parts of toughening agent, 0.1-1 parts of lubricant and 0.1-1 parts of antioxidant.
2. The high-strength nylon composite material according to claim 1, characterized in that: The nylon is at least one of nylon 6 and nylon 66.
3. The high-strength nylon composite material according to claim 1, characterized in that: The preparation method of the modified graphene oxide specifically comprises the following steps: S11. adding graphene oxide to N,N-dimethylformamide and dispersing by ultrasonication to obtain a graphene oxide dispersion; S12. dissolving 4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride in N,N-dimethylamide to obtain a 4,4'-diaminobiphenyl solution and a 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution; S13. placing graphene oxide in a reactor, adding 4,4'-diaminobiphenyl solution under nitrogen protection, stirring evenly, adding 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride solution dropwise under ice bath conditions, heating to room temperature, stirring to react for 1-2h, and continuing to heat to 65°C, reacting for 4-5h to obtain a reaction solution; S14. The reaction solution is cooled to room temperature, then poured into deionized water for precipitation, filtered, washed, and dried to obtain modified graphene oxide.
4. The high-strength nylon composite material according to claim 3, characterized in that: During the preparation process, the molar ratio of 4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride is 1:1; the amount of graphene oxide used is 10-40% of the total weight of 4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride.
5. The high-strength nylon composite material according to claim 1, characterized in that: The preparation method of the modified glass fiber is specifically as follows: S21. The glass fiber was immersed in a 5% sodium hydroxide solution for 2-3h and dried to obtain a pretreated glass fiber; S22. The pretreated glass fiber is transferred to a zinc acetate solution and subjected to a hydrothermal reaction for 4-5 hours to obtain a pre-modified glass fiber; S23. adding dopamine to pH 8.5 Tris buffer to obtain a dopamine solution; Dissolving maleic anhydride in dimethyl sulfoxide to obtain a maleic anhydride solution; The maleic anhydride solution is added to the dopamine solution, and the mixture is stirred under nitrogen protection, and then dimethyldiallylammonium chloride and ammonium persulfate are added to obtain a modified solution; S24. Soak the pre-modified glass fiber in the modifying liquid, heat and stir, and then wash and dry to obtain the modified glass fiber.
6. The high-strength nylon composite material according to claim 5, characterized in that: In step S22, the concentration of zinc acetate is 0.1 M, and the reaction temperature is 65-75°C.
7. The high-strength nylon composite material according to claim 5, characterized in that: In step S23, the dopamine concentration is 1.5-2 mol / L; the maleic anhydride concentration is 1-1.5 mol / L; the molar ratio of dopamine, maleic anhydride and dimethyldiallyl ammonium chloride is 1:(1-1.5):(0.5-1.5); and the amount of ammonium persulfate used is 3-8% by weight of the total amount of dopamine and dimethyldiallyl ammonium chloride used.
8. The high-strength nylon composite material according to claim 5, characterized in that: In step S24, the heating temperature is 40-60° C. and the stirring time is 10-30 min.
9. The high-strength nylon composite material according to claim 1, characterized in that: The toughening agent is at least one of polyoctene-maleic anhydride grafted product, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer grafted glycidyl acrylate copolymer; The lubricant is at least one of ethylene bis stearamide, silicone powder, and pentaerythritol stearate; The antioxidant is at least one of hindered phenols or phosphorus-containing antioxidants.
10. A method for preparing the high-strength nylon composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. preparing modified graphene oxide; S2. Preparation of modified glass fiber; S3. Put nylon, modified graphene oxide, modified glass fiber, toughening agent, lubricant and antioxidant into a mixer and mix them evenly. Then add the mixture into the feeding port of a twin-screw extruder. The six-section temperatures in the twin-screw extruder are 210°C, 220°C, 230°C, 230°C, 220°C and 210°C. After extrusion and granulation, a high-strength nylon composite material is obtained.
Citation Information
Patent Citations
Graphene / glass fibre reinforced nylon composite material and preparation method thereof
CN105778481A
Method for preparing high-performance glass fiber / graphene nylon 6 composite material
CN109161188A
Modified PA compound material and production method thereof
CN109971164A
High-strength heat-conducting nylon composite material and preparation method and application thereof
CN110358294A
Reinforced nylon material as well as preparation method and application thereof
CN114437539A